Developing a taxonomic framework for creativity in a problem-solving context: a research in the higher education context - Chai, Xun Yu (2022)
Creativity has been recognised as one of the most important skills in the 21st century. Although creativity has been advocated in the context of education, there still seems to be a lack of understanding of the concept of creativity, leading to teaching and learning practices that still encourage uniformity and conformity. The current literature on creativity is insufficient for understanding creativity from a more comprehensive manner, as frameworks and taxonomies for creativity largely focus on either listing a set of components relevant to creativity without explaining strategies that invoke creativity or categorising creative strategies without explaining the factors that support the use of these strategies, and the result of applying these strategies. More importantly, these frameworks are largely theoretical without empirical evidence. While there have been studies that investigate approaches for developing creativity, the effectiveness of these approaches is measured based on the improvement demonstrated through the creative outputs produced by the participants, by mainly looking at the number of solutions being produced and the originality of the solutions. They do not examine the use of strategies in the creative processes. As such, the understanding of how creativity can be supported by the use of set of strategies remains insufficient. In view of these situations, this study aimed to develop a taxonomic framework that could facilitate the understanding and development of creativity, which could serve as a foundation for teaching, learning and assessment. This study viewed creativity from the problem-solving perspective, where problems act as a catalyst for creative thinking.